RUQIYAH IN THE PERSPECTIVE OF ISLAMIC FIQH - Sarbini Anim (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
Ruqyah is understood as a treatment in the style of the Prophet SAW to eliminate diseases that originate from outside humans, people call it trance due to the entry of jinn and devils in humans. If this ruqyah is only understood as an appropriate solution to eliminate mental illness. So this research is on the contrary, that this ruqyah not only serves to cure psychological diseases that come from jinn disorders but also cures diseases caused by physical diseases, such as cancer, lung, kidney, diabetes and other diseases that afflict the human body. The issue of ruqyah has caused a lot of misunderstanding among the people. They consider that all ruqyah is permissible and correct, even though it cannot be separated from the role of the media in presenting and displaying the figure of a person who is powerful, great, has advantages, is able to ward off jinn, and even has congregations or followers. When assessing the phenomena that occur in Indonesia, it is not difficult to find and find people who are smart, and dress like kyai who practice shamanism. Their appearance is wrapped with Islamic appearance to make it seem right. Ruqyah Syar`iyyah is an Islamic treatment that uses the recitation of the Qur'an, dhikr, and prayer. Diseases that can be cured by ruqyah syar'iyyah with Allah's permission are physical and mental illnesses, or physical and mental illnesses, in other words physical or mental illnesses. The basis of Islamic healing lies in the Qur'an and the hadith of the prophet. Even though there are arguments, Islam's attitude towards Rukiah can be divided into three parts: Dalil, Tafris, and Mutadil. Asking for meruqyah is only allowed for patients who are suffering from the law, but peruqyah for circumcision helps those who seek help. The scholars use this Rukiyah with the holy verses of the Qur'an, believe that humans are only intermediaries, and agree that the problem of healing is the permission of Allah SWT. The Prophet practiced three sacred medicines: Ruqyah Sayar'iyyah, Thabi'iyyah, and Al Jam'u bainahuma. All three are integrated in one system called Thibbun Nabawi. With Allah's permission, Rukiyah healed the sick and alerted those who were previously unconscious. In our area known as the Qur'an, Dhikr, Bata Tamba, which means treating shamanism by using the holy book of prayer. Currently, the term Ruqyahs yar'iyyah is popular. Ruqyah is currently practiced or practiced on television, YouTube and in certain locations that offer official treatment. Besides Rukiyah who is sick, there are healthy people who know and suspect that Jin is there, so ask for Rukiyah. Eventually, he passed out as if possessed by a ghost, and after reading Rukiyah's recitation, some vomited and urinated. This situation contradicted Rukiyah's goal of healing the sick and awakening the unconscious. The unconscious person is forced to faint (a kind of trance). Of course, if he had died at that time, he would have forgotten Allah. Ruqyah dipahami sebagai pengobatan ala Rasulullah SAW untuk menghilangkan penyakit yang bersumber dari luar diri manusia, orang menyebutnya dengan kesurupan dikarenakan masuknya jin, dan syetan pada diri manusia. Apabila ruqyah ini hanya dipahami sebagai sebuah solusi yang tepat untuk menghilangkan penyakit psikis. Maka penelitian ini sebaliknya, bahwa ruqyah ini tidak hanya berfungsi untuk menyembuhkan penyakit psikis yang berasal dari gangguan jin saja tetapi juga menyembuhkan penyakit-penyakit yang disebabkan penyakit fisik, seperti kanker, paru-paru, ginjal, diabetes dan penyakit lainnya yang menimpa tubuh manusia. Persoalan ruqyah banyak menimbulkan kesalahfahaman di kalangan masyarakat masyarakat. Mereka menilai bahwa semua ruqyah itu boleh dan benar, padahal itu tidak lepas dari peran media yang menyuguhkan dan menayangkan sosok seeorang yang sakti, hebat, punya kelebihan, mampu menangkal jin, dan bahkan mempunyai jama’ah atau pengikut. Ketika menilai fenomena yang terjadi di Indonesia, maka tidak sulit menemui dan mencari orang yang pintar, dan berpakaian seperti kyai yang menjalankan praktik perdukunan. Penampilan mereka dibungkus dengan penampilan Islami agar terkesan benar. Ruqyah Syar`iyyah adalah pengobatan Islami yang menggunakan bacaan Al-Qur'an, dzikir, dan doa. Penyakit yang dapat disembuhkan dengan ruqyah syar'iyyah dengan izin Allah adalah penyakit fisik dan mental, atau penyakit fisik dan mental, dengan kata lain penyakit fisik atau mental. Dasar penyembuhan Islam terletak pada Al-Qur'an dan hadits nabi. Meskipun ada dalilnya, sikap Islam terhadap Rukiah dapat dibagi menjadi tiga bagian: Dalil, Tafris, dan Mutadil. Meminta meruqyah hanya diperbolehkan untuk pasien yang menderita hukum, tetapi peruqyah untuk khitan membantu mereka yang mencari pertolongan. Para ulama menggunakan Rukiyah ini dengan ayat-ayat suci Al-Qur'an, percaya bahwa manusia hanyalah perantara, dan setuju bahwa masalah penyembuhan adalah izin Allah SWT. Nabi mempraktikkan tiga obat suci: Ruqyah Sayar'iyyah, Thabi'iyyah, dan Al Jam'u bainahuma. Ketiganya terintegrasi dalam satu sistem yang disebut Thibbun Nabawi. Dengan izin Allah, Rukiyah menyembuhkan orang sakit dan mengingatkan mereka yang sebelumnya tidak sadar. Di daerah kami dikenal dengan Al-Qur'an, Dzikir, Bata Tamba, yang artinya mengobati penyakit perdukunan dengan menggunakan kitab suci doa. Saat ini, istilah Ruqyahs yar'iyyah sedang populer. Ruqyah saat ini dipraktikkan atau dipraktikkan di televisi, YouTube, dan di lokasi tertentu yang menawarkan perawatan resmi. Selain Rukiyah yang sakit, ada orang sehat yang tahu dan curiga ada Jin, jadi mintalah Rukiyah. Akhirnya, dia pingsan seolah-olah dirasuki hantu, dan setelah membaca bacaan Rukiyah, beberapa muntah dan buang air kecil. Situasi ini bertentangan dengan tujuan Rukiyah untuk menyembuhkan orang sakit dan membangunkan orang yang pingsan. Orang yang tidak sadar dipaksa pingsan (semacam kesurupan). Tentu saja, jika dia meninggal pada saat itu, dia akan melupakan Allah.